“I Have Worn No Shoes upon This Holy Ground”: Hebrew and Religious Authority in Elizabeth Barrett Browning’s Poems (1838, 1844) - Gal Manor (Religions)
This paper will delineate Elizabeth Barrett Browning’s (EBB) allusions to Hebrew in her writing, both personal and public, and her ambivalent attitude towards the Hebrew language and how it is related to her views on poetry and religious identity. Although most critics have focused on EBB’s knowledge of Greek, her use of Hebrew, whether translated, transliterated, or presented in the original Hebrew characters, reveals her concept of poetic language and her core religious beliefs. In her collections of poems published in 1838 and 1844, EBB reiterates her concept of Hebrew as a sacred language, a language endowed with what Bourdieu would term symbolical capital, and superior to other languages. However, her correspondence reveals an ambivalence towards Hebrew: it is a “primitive” language that she does not wish to be associated with on the one hand and revered in relation to Spiritualism and the medium George Bush on the other. Finally, the appearances of Hebrew in her works constitute what Derrida terms a poetic Shibboleth, meant to define who is to be accepted into the realm of sacred poetry and who is to be left out. Ironically, it is the anxiety around this double-edged Shibboleth that ultimately brings about the disappearance of Hebrew letters from EBB’s poems written after 1844.